Binding to the neonatal Fc receptor enhances the pathogenicity of anti-desmoglein-3 antibodies in keratinocytes - Zakrzewicz, Anna; Vanderheyden, Katrien; Galaly, Yad; Feldhoff, Simon; Sips, Magdalena; Brinkhaus, Maximilian; Tikkanen, Ritva (Frontiers in Immunology, 2024)
The neonatal Fc receptor (FcRn) is important for numerous cellular processes that involve antibody recycling and trafficking. A major function of FcRn is IgG recycling and half-life prolongation, and FcRn blockade results in a reduction of autoantibodies in IgG-mediated autoimmune diseases. In epithelial cells, FcRn functions in processes different from IgG recycling, such as antibody transcytosis in intestinal cells. In pemphigus vulgaris, an autoimmune disease of the epidermis, IgG autoantibodies directed against desmosomal adhesion proteins, especially desmoglein-3 and -1, cause loss of keratinocyte adhesion. We have previously demonstrated that FcRn blockade with efgartigimod, a human Fc fragment with enhanced FcRn binding, significantly reduces the keratinocyte monolayer fragmentation caused by anti-desmoglein-3 antibodies. This points to a direct function of FcRn in keratinocytes, beyond IgG recycling, but the mechanisms have not yet been elucidated in detail. Here, we show that FcRn binding is required for the full pathogenicity of recombinant anti-desmoglein-3 antibodies in keratinocytes, and that antibodies that exhibit enhanced or reduced FcRn affinity due to targeted substitutions in their Fc region, as well as F(ab')2 fragments not binding to FcRn display different degrees of pathogenicity. Blockade of FcRn by efgartigimod only shows a protective effect on keratinocyte adhesion against antibodies capable of binding to FcRn. Furthermore, antibody-induced degradation of desmoglein-3 in keratinocytes does not depend on FcRn, demonstrating that desmoglein-3 degradation and acantholysis are functionally disconnected processes. Our data suggest that the role of FcRn in autoimmune diseases is likely to be versatile and cell-type dependent, thus stressing the importance of further studies on FcRn function in autoimmune diseases.